GLYCEMIC CONTROL AND COMPLICATIONS IN TYPE 2 DIABETICS ATTENDING PUBLIC HOSPITALS IN PAKISTAN - Dr. Muhammad Salman Khan; Dr. Waqas Ahmed; Dr. Sher Alam Khan; Dr. Hassan Ejaz (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Introduction: Type 2 diabetes mellitus (T2DM) is a growing public health concern in Pakistan, with poor glycemic control contributing significantly to the development of microvascular and macrovascular complications. Despite increasing prevalence, data on glycemic control and complication rates in public hospital settings remain limited. Objective: To assess glycemic control and the prevalence of diabetes-related complications among patients with T2DM attending a public tertiary care hospital in Abbottabad, Pakistan. Materials and Methods: A cross-sectional study was conducted at Ayub Teaching Hospital Abbottabad, Pakistan, from November, 2020 to April, 2021. Adult T2DM patients attending outpatient clinics were enrolled. Glycemic control was assessed using HbA1c levels, and diabetes complications were documented through clinical evaluation and medical records. Results: Among 300 patients, 78.1% exhibited poor glycemic control (HbA1c ≥7%). Microvascular complications, including retinopathy (44.4%), neuropathy (36.9%), and nephropathy (31.6%), were common. Macrovascular complications, such as ischemic heart disease (27.8%) and stroke (8.8%), were also prevalent. Longer duration of diabetes was significantly associated with higher complication rates. Conclusion: Poor glycemic control and high complication rates in T2DM patients attending public hospitals highlight the urgent need for integrated diabetes management programs, emphasizing patient education, regular monitoring, and multidisciplinary care to improve outcomes in Pakistan.